Applying self-determination theory to behavior change technologies: insights from two projects in the health domain - Gerstenberg, Rebecca; Høeg, Emil Rosenlund; Van der Kaap-Deeder, Jolene; Hassenzahl, Marc (Frontiers in Psychology, 2025)
In the health domain, patients often need to adopt and maintain behaviors that are tedious, unpleasant, or even painful, such as taking medication regularly, being more physically active, or maintaining a diet. Behavior change technologies (BCTs) can play a crucial role in instilling change and maintaining healthy behaviors. One psychological theory to guide the design of BCTs is Self-Determination Theory (SDT). However, researchers within Human-Computer Interaction (HCI) struggle with its application, as the field lacks a shared understanding and reflection on the use of SDT. We present two HCI research projects in the health domain and reflect on the role SDT played in their implementation. Through a comparative analysis, we found that SDT was helpful in providing an analytical focus and guiding quantitative evaluations. However, its adaptation to qualitative methods and explicit design guidelines presents difficulties. Our reflection underscored the potential of SDT as both a theoretical lens and practical design tool for developing autonomy-supportive health technologies.